DELIBERATIVE DEMOCRACY IN THE DEVELOPMENT PLAN CONSTRUCTION OF SEMAMBU ISLAND VILLAGE, INDRALAYA UTARA DISTRICT, OGAN ILIR REGENCY - Mardianto, Mardianto; Susilawati, Retno; Saptawan, Ardiyan; Khairunnas, Khairunnas; Rafinzar, Rahmat (DIA: Jurnal Administrasi Publik, 2022)
The background of the research is to analyze the application of deliberative democracy in the implementation of the Village Development Planning deliberations in Pulau Semambu Village, North Indralaya District, Ogan Ilir Regency. The research method used is a qualitative research method with a descriptive approach. Data collection techniques were carried out through interviews, observations, and literature studies. The data were analyzed using an interactive model technique. The data analysis carried out was strengthened by using the NVivo 12 Plus supporting software. The selection of informants was done through the purposive sampling technique and the use of the source triangulation method to measure the validity of the data. The results of the study show that deliberative democracy has not been implemented optimally due to the lack of public understanding regarding development and the Musrenbangdes, so it has an impact on the low participation of the people involved. In addition, budget constraints and the lack of open dialogue are also other problems that become an evaluation of the implementation of the Musrenbangdes that have been implemented. so that the study of village problems and needs is not carried out in depth. Overall causes the principles of deliberative democracy have not been achieved optimally prioritizing community participation. To realize a deliberative village policy formulation process, the village government can take various approaches such as involving academics to assist the Musrenbangdes process. The government also needs to provide space for the widest possible community to be actively involved in the Musrenbangdes process through the availability of an open dialogue forum.